2009
DOI: 10.1021/cc900059q
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Nanoscanning, Bead Picking (CONA): PickoScreen Microscopes for Automated and Quantitative Screening of One-Bead One-Compound Libraries

Abstract: Solid phase combinatorial chemistry provides fast and cost-effective access to large bead based libraries with compound numbers easily exceeding tens of thousands of compounds. Incubating one-bead one-compound library beads with fluorescently labeled target proteins and identifying and isolating the beads which contain a bound target protein, potentially represents one of the most powerful generic primary high throughput screening formats. On-bead screening (OBS) based on this detection principle can be carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…The on-bead screens of the mixed αβ phosphopeptide libraries were carried out following previously described procedures [8]. Briefly, confocal nanoscanning, CONA, is a fully automated and quantitative on-bead screening process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The on-bead screens of the mixed αβ phosphopeptide libraries were carried out following previously described procedures [8]. Briefly, confocal nanoscanning, CONA, is a fully automated and quantitative on-bead screening process.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the distribution of hit beads and the analysis of the fluorescence intensity of bead-bound Cy5-SAP within the sublibraries, a total of 48 beads from 13 wells were isolated using the bead-picking device on the PS04 instrument [8]. All retrieved hit beads were placed into separate glass vials for subsequent fluorescence labelling.…”
Section: Hit Analysis and Bead Pickingmentioning
confidence: 99%
“…The small (10 μm) TentaGel beads employed for library construction both facilitate large library synthesis (each gram of resin contains 1000-fold more 10-μm beads than conventional 90-μm beads) and the use of FACS-based screening, which quantitatively analyzes and collects several thousand compound beads per second. This represents a vast improvement over manual bead picking, which is slow, manual, and subjective in the absence of custom screening technology 29 . The greatly enhanced throughput of NGS-based structure elucidation uniquely provided rapid and deep analysis of hit structures, critical for matching the throughput of FACS 30 .…”
Section: Discussionmentioning
confidence: 99%
“…After completion of the scan, the hits are ranked by their intensities, and the best are picked by an actuated capillary and placed into individual containers for structural evaluation. The bead picking process is slower and can retrieve about 1 bead/min [280][281][282]. Resynthesis and retesting of the active compounds has shown that surface inhomogeneity prevents precise ranking of the ligand quality based on the solid support fluorescence reading (Figure 12.10).…”
Section: Synthesis Of Peptides On a Mixture Of Particlesmentioning
confidence: 99%
“…Observation of increased ring intensity represents the binding to macromolecular fluorescently labeled target. Fluorescence in the middle of the bead represents autofluorescence of the bead material or synthesized compound and is irrelevant to the biological interaction with the target[280].…”
mentioning
confidence: 99%